THE LANDSCAPE OF PHYSICS SUBJECT EDUCATION IN ASEAN COUNTRIES: A BIBLIOMETRIC STUDY - Syed Taufiq Akmal Syed Nasiruddin; Ainorkhilah Mahmood; Nur Maizatul Azra Mukhtar; Nur Iwani Nor Izaham; Mahayatun Dayana Johan Ooi; M Ahmed, Naser, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study examines the research encompassing physics subject education conducted between 2000 and 2023, sourced from the Web of Science database using bibliometric analysis. The paper's objective is to analyse the evolving research landscape surrounding physics subject education in the ASEAN countries. While previous studies have explored the area of physics education on a global scale, this research offers a more focused analysis, exclusively focusing on the ASEAN nations. To accomplish this, an array of bibliometric analysis tools, including MS Excel, VOSviewer, and Harzing’s Publish or Perish software, were used. Performance analysis was done and named based on the subsection. The study’s findings unveil a trend that exhibited an upward total publication trajectory from 2014 to 2020, followed by a gradual decline from 2021 to 2023. Indonesia’s substantial contributions account for an astounding 81.5% of total ASEAN publications, spanning both influential and prolific organization categories. Among the top authors were from Singapore, Indonesia, Malaysia and Thailand. From the authorship section, the collaborative nature of researchers within ASEAN countries can be seen, particularly those who share common affiliations. The funding shows that only 30.1% of overall physics subject education publications in ASEAN are funded. Finally, the keyword analysis shows the patterns highlighting its evolving interaction with technological advancements. This marks a compelling transformation within the sphere of physics subject education landscape, providing valuable insights for educators, researchers, and policymakers to assess their performance and indicators to assess the nation's educational initiatives and their impact on various aspects of physics subject education.